Study of In vitro antioxidant and DNA damage protection activity of a novel luteolin derivative isolated from Terminalia chebula. Issue 1 (11th December 2019) - Soumya, K.; Haridas, Karickal R.; James, Jesna; Sameer Kumar, V. B.; Edatt, Lincy; Sudheesh, S.
ABSTRACT: The present study aimed to investigate the efficacy of flavonoids isolated from the fruit of Terminalia chebula against the hydrogen peroxide-induced DNA damage. Five fractions were screened and were compared for their in vitro antioxidant activity by DPPH method and DNA protection activity by DNA nicking assay. All the extracts showed excellent antioxidant activity with IC50 values ranging from 11.23 ± 0.18 to 36.70 ± 0.12 µg/ml. The band intensity of supercoiled, circular and linear DNA was measured in DNA nicking assay and it is very clear that the addition of extract significantly inhibited the formation of circular and linear forms of DNA. Methanol–Water 1:1 fraction which showed the highest activity in antioxidant and DNA protection was subjected to structural characterization using different spectroscopic techniques. The structure of the compound was identified as a derivative of luteolin. The result presented in this work strongly supports the hypothesis that DNA protection activities were positively associated with the antioxidant property.